The animated man : a life of Walt Disney - Barrier, J. Michael (University of California Press, 2007)
Walt Disney (1901-1966) was one of the most significant creative forces of the twentieth century, a man who made a lasting impact on the art of the animated film, the history of American business, and the evolution of twentieth-century American culture. He was both a creative visionary and a dynamic entrepreneur, roles whose demands he often could not reconcile. In his compelling new biography, noted animation historian Michael Barrier avoids the well-traveled paths of previous biographers, who have tended to portray a blemish-free Disney or to indulge in lurid speculation. Instead, he takes the full measure of the man in his many aspects. A consummate storyteller, Barrier describes how Disney transformed himself from Midwestern farm boy to scrambling young businessman to pioneering artist and, finally, to entrepreneur on a grand scale. Barrier describes in absorbing detail how Disney synchronized sound with animation in Steamboat Willie; created in Snow White and the Seven ...
Keywords: Disney, Walt, -- 1901-1966.; Disney, Walt, -- 1901-1966; Disney, Walt -- 1901-1966; Disney, Walt.; Animators -- United States -- Biography.; Animateurs (Cinéma) -- États-Unis -- Biographies.; PERFORMING ARTS -- Film & Video -- Reference.; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts.; PERFORMING ARTS -- Film & Video -- General.; Animators; United States; Animatiefilms.; Verenigde Staten.; Animators -- Biography.; 20th century american animation.; 20th century american culture.; 20th century american history.; american business.; american culture.; animated films.; biography.; cartoon characters.; cartoons.; disney animation.; disney company.; disney studios.; disney.; disneyland.; entrepreneur.; mickey mouse.; midwest.; promotional.; rural missouri.; snow white.; snow with and the seven dwarfs.; steamboat willie.; television.; walt disney world.; walt disney.; Biography; Biographies; Biographies.